PENTINGNYA EKSPOSUR PERUSAHAAN SEKTOR ENERGI UNTUK MENEMPUH PENGUNGKAPAN EMISI KARBON - Khotimah, Siti; Sari, Shinta Permata (Media Mahardhika, 2024)
Carbon emission disclosure is one of the important components in the disclosure made by a company. Its disclosure is required to assess the company's responsibility to the environment that will increase the value and reputation of the company. This study aims to examine the effect of media exposure, ISO 14001 certification, environmental performance, and auditor credibility on carbon emission disclosure. The population in this study are companies listed on the Indonesia Stock Exchange in 2018-2022. The sample in this study are energy sector companies listed on the Indonesia Stock Exchange in 2018-2022 which are taken using purposive sampling technique and obtained 19 samples with 95 observations. The type of data used is secondary data. This research uses multiple linear regression analysis methods to analyse the hypothesis. Based on the results of regression analysis with a significance level of 5%, this study concludes that ISO 14001 certification and environmental performance have effect on carbon emission disclosure, while media exposure and auditor credibility have no significant effect on carbon emission disclosure.